The effect of the teacher preparation program in the College of Education on student teachers' acquisition of professional competencies in relation to their attitudes towards the teaching profession - Nasser Al rwahi; Suliman Al Balushi (Journal of Educational and Psychological Studies, 2011)
The aims of the current study were to measure student teachers' acquisition level of professional competencies from their point of view, to determine the most influential elements of the teacher preparation program on the acquisition of these competencies, and to study the relationship between the acquisition of these competencies and the student teachers' attitudes towards the teaching profession. The sample included ١٦٧† student teachers in the College of Education at Sultan Qaboos University. Two instruments were designed: one to measure the professional competencies and other to measure the attitudes towards the teaching profession. The two instruments were uploaded on the internet for the purpose of data collection. The results showed that in the view of student teachers, the teaching competencies were most important with the highest ranking, and the evaluation competencies came last. Regarding the most influential elements of the teacher preparation program, the teaching practicum came first, then the curriculum and instruction courses, and then the psychology courses. Also, from the student teachers' point of view, the level of influence the foundation and administration courses was weak. The females outperformed males in preparation and teaching competencies. However, there were no significant differences among the means of the competencies or in the overall means. The females also displayed more positive in attitudes towards the teaching profession. In general, the student teachers' attitudes towards teaching were moderate; however, the relationship between the acquisition of the professional competencies and the attitudes towards the teaching profession was statistically significant.